2007
DOI: 10.1016/j.jpaa.2006.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Star stable domains

Abstract: We introduce and study the notion of -stability with respect to a semistar operation defined on a domain R; in particular we consider the case where is the w-operation. This notion allows us to generalize and improve several properties of stable domains and totally divisorial domains. MSC: Primary: 13A15; secondary: 13F05; 13G05 IntroductionStar operations, such as the v-closure (or divisorial closure), the t-closure and the w-closure, are an essential tool in modern multiplicative ideal theory for characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…When Stability with respect to star operations (and more generally to semistar operations) was introduced and studied by the authors of this paper in [16].…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…When Stability with respect to star operations (and more generally to semistar operations) was introduced and studied by the authors of this paper in [16].…”
Section: 2mentioning
confidence: 99%
“…Recall that a Prüfer domain (resp., a PvMD) is called strongly discrete if P = P 2 for each prime (resp., t-prime) ideal P . A domain is integrally closed and Clifford w-regular (resp., w-stable) if and only if it is a PvMD (resp., a strongly discrete PvMD) with t-finite character [17,Corollary 4.5], [16,Therem 2.9]. Thus, for w = d, an integrally closed Clifford regular (resp., stable) domain is precisely a Prüfer domain (resp., a strongly discrete Prüfer domain) with finite character [5,Theorem 4.5], [32,Theorem 4.6].…”
Section: 2mentioning
confidence: 99%
“…Here we mainly consider the cases where * = d, w, t. In fact the most interesting results on star stability and star regularity were obtained in [15] and [16] for star operations spectral and of finite type. In addition, if * is spectral and of finite type, * -regularity implies * = w [16,Corollary 1.7]; in particular, if R is Clifford regular, then w = d.…”
Section: Introductionmentioning
confidence: 99%
“…In my conference talk, based on [8,9,10], I showed that many properties of stability and Clifford regularity can be generalized and improved in the set of (semi)star operations. In particular, by using the techniques developed in [9], the results illustrated in the next section can be proved for star regularity with respect to any star operation that is spectral and of finite type (see [9] for the relevant definitions).…”
Section: Introductionmentioning
confidence: 99%